PENERAPAN TEKNOLOGI MESIN PENGAYAKAN TIPE-ROTARY UNTUK PEMISAHAN DEDAK HALUS, DEDAK KASAR, DAN MENIR PADA INDUSTRI UMKM PENGOLAHAN PAKAN TERNAK - B, Badruzzaman; M Azwar, M Azwar; Aziz, Aziz; PB, Pandu (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2024)
MSMEs engaged in animal feed processing in the Indramayu area still use the bran sieving process using 2 machines, namely a sieving machine and a fanning machine. This process functions to separate the bran raw material into fine bran, coarse bran and groats. This requires a machine solution that unites the 2 machines. The aim of making this machine is to produce a more efficient and effective machine so that the quality of the final product increases and production time is shorter. Implementation methods start from problem identification, literature study, observation, design, simulation, preparation, manufacture, machine assembly, machine testing, application to MSMEs, as well as activity evaluation and outreach/training. The results obtained are that this machine has frame dimensions of length 2100 mm × width 790 mm × 1250 mm, material is ASTM A36 angle iron, 1 phase 1 HP electric motor, motor rotation 2800 rpm and transmitted by v-belt to the gearbox with a ratio of 1: 10 produces a rotation of 280 rpm. The product manufacturing process has been successfully carried out through 2 machine tests, namely the function test which states that all components can function properly, while the performance test states that the separation of coarse bran produced is 54%, fine bran 35.4%, and groats 10.6%. The separation of bran has been carried out optimally, and the process of separating 5 kg of bran takes 3.09 minutes, the capacity of the sieving machine is 97 kg/hour. Finally, this rotary-type sieving machine is expected to increase the productivity and quality of the animal feed processing industry in Indramayu Regency.